Halakhic Man - Soloveitchik, Joseph Dov, 1903-1993 (Book collections on Project MUSE., 2023)
"The 40th Anniversary Edition of Halakhic Man is the classic work of modern Jewish and religious thought by the twentieth century's preeminent Orthodox Jewish theologian and talmudic scholar, newly accompanied by scholarly apparatus that will help readers better appreciate the work"--